Colorimetric sensing array based on Fe single-atom nanozyme for ultrasensitively discriminating organophosphorus pesticides - Yi Yuan; Haibo He; Xiaojing Si; Junping Dong; Xitian Peng; Xiaoxia Yan; Liqiang Luo (Analytica Chimica Acta, 2026)

Comprehensive thermodynamic and kinetic studies on N-methylation and N-formylation during methacrolein synthesis via aldol reaction - Xiaoyan Zheng; Hanwen Yan; Junyang Liu; Jie Li; Junping Zhang; Songsong Chen; Hongnan Chen; Gang Wang; Chunshan Li (Chemical Engineering Journal, 2026)

Rogue waves in the northern part of the South China Sea: chaotic dynamics and multiparameter synergy determination - Tao Feng; Tianyu Zhang; Danchen Yan; Hailong Wang; Jian Yang; Xun Lin; Junping Zhang (Journal of Oceanology and Limnology, 2026)

Integration of spatial attention mechanism into 1D-CNN for prediction of wheat leaf nitrogen concentration from UAV-borne hyperspectral imagery - Jing Zhao; Hong Li; Junping Liu; Menglong Zhao; Zhaoxia Yan (Computers and Electronics in Agriculture, 2025)

Construction of the sea surface wind field of Typhoon Chaba based on wind field model and CMEMS data - Zijing Ou; Tianyu Zhang; Danchen Yan; Yulin Wang; Junping Zhang; Hao Ning; Cheng Chi; Lengjian Chen (Journal of Oceanology and Limnology, 2025)

Bioelectronic sutures with electrochemical glucose-sensing for real-time wound monitoring - Jiamin Yan; Junping Wang; Zhongdong Wu; Zihan Li; Zhihui Li; Zongqian Hu (Analytica Chimica Acta, 2025)

Characteristics of nitrogen and phosphorus migration at sediment-water interface in seasonal frozen lakes and the mechanism of microbial driven cycling: a case study of Lake Daihai - Rong Wu; Xiaohong Shi; Xueer Kang; Sheng Zhang; Shengnan Zhao; Yu Liu; Biao Sun; Junping Lu; Haifeng Yu; Shihuan Wang; Xueru Pan; Kaiqi Shen; et al. (Journal of Contaminant Hydrology, 2025)

Detection of arsenate in colored grains using an interference-free dual-signal ratiometric HEC sensor - Shao-Hua Wen; Ning Wang; Ziqi Yuan; Hao Wu; Gege Yan; Hengyuan Zhang; Sha Yu; Junping Ma; Yuanzhen Zhou (Food Chemistry, 2025)

Impact of lipid oxidation products on the digestibility and structural integrity of Myofibrillar proteins during thermal processing - Yingshuang Lu; Yuan Zhuang; Yu Jiang; Junping Wang; Lu Dong; Yan Zhang; Shuo Wang (Food Chemistry, 2025)

Inhibitory effects of berberine on fungal growth, biofilm formation, virulence, and drug resistance as an antifungal drug and adjuvant with prospects for future applications - Junping Ding; Zhong Yan; Liang Peng; Jing Li; Fuzhou Yang; Dongming Zheng (World Journal of Microbiology and Biotechnology, 2025)

Long-term exposure to advanced lipid peroxidation end products impairs cognitive function through microbiota-gut-brain axis - Yaya Wang; Dancai Fan; Yan Zhang; Junping Wang; Lu Dong; Yaozhong Hu; Shuo Wang (Food Chemistry, 2024)

Acetate-based ionic liquid immobilized Fe-MIL-101-NH2: A highly efficient heterogeneous catalyst for the conversion of CO2 into oxazolidinones with N-aryl epoxy amines - Junping Niu; Guanghui Wang; He Qiao; LiGang Yan; Jiakai Wu; Yuanyuan Gao; Limin Han; Ning Zhu (Journal of Environmental Chemical Engineering, 2024)

MS2/GmAMS1 encodes a bHLH transcription factor important for tapetum degeneration in soybean - Junping Yu; Yan Xu; Yuanyuan Huang; Yuxue Zhu; Lulu Zhou; Yunpeng Zhang; Bingyao Li; Hao Liu; Aigen Fu; Min Xu (Plant Cell Reports, 2024)

Evolution of vegetation cover and impacts of climate change and human activities in arid regions of Northwest China: a Mu Us Sandy Land case - Jing Lin; Wenhao Bo; Xinping Dong; Ruiwan Zhang; Junping Yan; Tao Chen (Environment, Development and Sustainability, 2024)

Effects of intracellular Ca2+ on developmental potential and ultrastructure of cryopreserved-warmed oocyte in mouse - Junping Cheng; Xiaoli Wang; Chan Luo; Xianbao Mao; Jie Qin; Yan Chi; Bing He; Yanrong Hao; Xiangli Niu; Ben Huang; Liling Liu (Cryobiology, 2024)

“Fluorescence-wavelength” label-free POCT tandem with “fluorescence-photothermal” nanobody-immunosensor for detecting BSA and β-lactoglobulin - Shijie Li; Linqing Nie; Lu Yang; Dancai Fan; Junping Wang; Yaozhong Hu; Yan Zhang; Shuo Wang (Food Chemistry, 2024)

Comparison of structure and neuroprotective ability of low molecular weight galactomannans from Sesbania cannabina obtained by different extraction technologies - Bowen Yan; Junping Deng; Jie Gu; Yuheng Tao; Caoxing Huang; Chenhuan Lai; Qiang Yong (Food Chemistry, 2023)

Detection of β-lactoglobulin under different thermal-processing conditions by immunoassay based on nanobody and monoclonal antibody - Shijie Li; Linqing Nie; Yi Wang; YaYa Wang; Dancai Fan; Junping Wang; Yaozhong Hu; Lu Dong; Yan Zhang; Shuo Wang (Food Chemistry, 2023)

Immune-Ageing Evaluation of Peripheral T and NK Lymphocyte Subsets in Chinese Healthy Adults - Zhenghu Jia; Zhiyao Ren; Dongmei Ye; Jiawei Li; Yan Xu; Hui Liu; Ziyu Meng; Chengmao Yang; Xiaqi Chen; Xinru Mao; Xueli Luo; Zhe Yang; et al. (Phenomics, 2023)
Ageing is often accompanied with a decline in immune system function, resulting in immune ageing. Numerous studies have focussed on the changes in different lymphocyte subsets in diseases and immunosenescence. The change in immune phenotype is a key indication of the diseased or healthy status. However, the changes in lymphocyte number and phenotype brought about by ageing have not been comprehensively analysed. Here, we analysed T and natural killer (NK) cell subsets, the phenotype and cell differentiation states in 43,096 healthy individuals, aged 20–88 years, without known diseases. Thirty-six immune parameters were analysed and the reference ranges of these subsets were established in different age groups divided into 5-year intervals. The data were subjected to random forest machine learning for immune-ageing modelling and confirmed using the neural network analysis. Our initial analysis and machine modelling prediction showed that naïve T cells decreased with ageing, whereas central memory T cells (Tcm) and effector memory T cells (Tem) increased cluster of differentiation (CD) 28-associated T cells. This is the largest study to investigate the correlation between age and immune cell function in a Chinese population, and provides insightful differences, suggesting that healthy adults might be considerably influenced by age and sex. The age of a person's immune system might be different from their chronological age. Our immune-ageing modelling study is one of the largest studies to provide insights into ‘immune-age’ rather than ‘biological-age’. Through machine learning, we identified immune factors influencing the most through ageing and built a model for immune-ageing prediction. Our research not only reveals the impact of age on immune parameter differences within the Chinese population, but also provides new insights for monitoring and preventing some diseases in clinical practice.

Time frequency domain combined deconvolution method - Wei Zhou; Huailai Zhou; Dan Long; Haitao Yan; Junping Liu (Acta Geophysica, 2023)

Recycling of iron ore tailings into magnetic nanoparticles and nanoporous materials for the remediation of water, air and soil: a review - Xiaoyu Han; Fei Wang; Yan Zhao; Junping Meng; Guangyan Tian; Lijuan Wang; Jinsheng Liang (Environmental Chemistry Letters, 2023)

Kinetic and mechanistic insights into the roles of protonated morpholine species and weak acidic environment in methylacrolein production catalyzed by morpholine/acid - Qiu Zhao; Hui Zhao; Gang Wang; Hanwen Yan; Junping Zhang; Xinyue Liu; Yijun Cao (Chemical Engineering Journal, 2023)

A techno-economic analysis of bio-gasoline production from corn stover via catalytic conversion - Dongxia Yan; Junping Zhang; Xingmei Lu; Qing Zhou; Junli Xu; Jiayu Xin (Clean Technologies and Environmental Policy, 2021)

Is there a regularity: the change of arable land use pattern under the influence of human activities in the Loess Plateau of China? - Jun Zhang; Junping Yan; Liang Xue; Yuanzhi Yao; Xin Shu (Environment, Development and Sustainability, 2021)

Spatio-temporal variations of the flood mitigation service of ecosystem under different climate scenarios in the Upper Reaches of Hanjiang River Basin, China - Pengtao Wang; Liwei Zhang; Yingjie Li; Lei Jiao; Hao Wang; Junping Yan; Yihe Lü; Bojie Fu (Journal of Geographical Sciences, 2018)

Mapping the hotspots and coldspots of ecosystem services in conservation priority setting - Yingjie Li; Liwei Zhang; Junping Yan; Pengtao Wang; Ningke Hu; Wei Cheng; Bojie Fu (Journal of Geographical Sciences, 2017)

The relationship between precipitation heterogeneity and meteorological drought/flood in China - Yonglin Liu; Junping Yan; Minyi Cen (Journal of Meteorological Research, 2016)

A graded index for evaluating precipitation heterogeneity in China - Yonglin Liu; Junping Yan; Minyi Cen; Qunsheng Fang; Zhengyao Liu; Yingjie Li (Journal of Geographical Sciences, 2016)

Neutrophils Play a Crucial Role in the Early Stage of Nonalcoholic Steatohepatitis via Neutrophil Elastase in Mice - Shufei Zang; Lei Wang; Xiaojie Ma; Geli Zhu; Zhenjie Zhuang; Yunhao Xun; Falin Zhao; Wenjun Yang; Juan Liu; Yan Luo; Yinlan Liu; Dewei Ye; et al. (Cell Biochemistry and Biophysics, 2015)

Response of vegetation restoration to climate change and human activities in Shaanxi-Gansu-Ningxia Region - Shuangshuang Li; Junping Yan; Xinyan Liu; Jia Wan (Journal of Geographical Sciences, 2013)